O PAPEL DO SUPREMO TRIBUNAL FEDERAL NA PRESERVAÇÃO DOS DIREITOS FUNDAMENTAIS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
For the recognition of a country such as a democratic state, effective preservation of the human rights established in the Constitution must occur. However, mere normative provision is not sufficient without the protection provided by the Constitutional Supreme Court. Therefore, this article will reflect on the role of the Brazilian Federal Supreme Court. In this sense, this work intends to answer the following question: what is the role of the Brazilian Supreme Court in the preservation of human rights? The main objective of this paper is to demonstrate the importance of judicial activism as aninstrument to preserve Human Rights, while the specific objective of this piece is to identify which situations that required the Brazilian Supreme Court's intervention, as well as analyze which human rights were protected. The methodology used was deductive, with bibliographic review, analysis of jurisprudence, study of doctrines and academic articles. In its conclusion it states the importance of the Brazilian Supreme Court as a counterpoint to possible strains and threats to institutional disruption.